A Comparison of Viscous Damper Placement Methods for Improving Seismic Building Design - Whittle, J; Williams, M; Karavasilis, T; Blakeborough, A (2012)
This article compares the effectiveness of five viscous damper placement techniques, two standard and three advanced, for reducing seismic performance objectives, including peak interstory drifts, absolute accelerations, and residual drifts. The techniques are evaluated statistically for two steel moment-resisting frames under varying seismic hazard levels, employing linear viscous dampers and nonlinear time history analyses. Usability of the methods is also assessed. All the placement methods meet the desired drift limit but advanced techniques achieve additional improvement in drift reduction and distribution. Performance differences between the advanced techniques are minor, making usability a significant selection factor amongst the methods. © 2012 Copyright A. S. Elnashai and N. N. Ambraseys.